Machine Acting and Contract Law – The Disruptive Factor of Artificial Intelligence for the Freedom Concept of the Private Law - Koos, Stefan (UIR Law Review, 2021)
Technologic evolutions of the last two decades, such as the development of the internet, had a strong disruptive effect to the society and the economy. However, because of the flexible concepts of the civil law codifications a disruptive effect in the private law until now did not exist. Especially the legal consequences of the internet were integrated into the private law without bigger categorial or structural changes. This applies equally to most of the cases of the use of artificial intelligence (AI) in recent times. With more advanced development of AI-systems, though, it may not be possible anymore to apply the traditional terms of the private law to the use of AI without leaving the constitutional law background of the private law. This article discusses the impact of the use of a future advanced independent AI on the concept of the private autonomy in the contract law. Furthermore, it gives an overview on the new legislative approach of a human centric use of AI in the European Union.